Proceedings of the 2018 8th International Conference on Manufacturing Science and Engineering (ICMSE 2018) 2018
DOI: 10.2991/icmse-18.2018.116
|View full text |Cite
|
Sign up to set email alerts
|

Hot air-assisted radio frequency heating treatment for controling Aflatoxin B1 on corn grains

Abstract: The best condition of hot air-assisted RF-heating treatment Aflatoxin B1 decontamination was 19.05% wb of initial grain moisture content with 80 °C for 20 minutes. Additionally, the RF-heating treatment also had the high efficiency on Aflatoxin B1 decontamination when applied under conditions: 80 °C for 20 minutes, and reduce to 69.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Earlier work done by Vearasilp et al (2015) showed around 64% reduction of aflatoxin B1 in Perilla frutescens L. highland oil seed when treated with RF under conditions of 90°C for 7–10 min. Also, the RF heating therapy exhibited a high efficiency on aflatoxin B1 decontamination with a reduction of 69.6% in corn grains (Zhang & Wei, 2018). In this study, the disinfection of contaminated peanuts was done at selected electrode height and conveyor speed combination to check the efficacy of RF against aflatoxins, and the obtained results (Table 6) showed that RF treatment is effective against aflatoxin B1 and B2, with a pronounced decrease of aflatoxin B1 and B2 of 92.64% and 90.51%, respectively, at 89.96°C.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work done by Vearasilp et al (2015) showed around 64% reduction of aflatoxin B1 in Perilla frutescens L. highland oil seed when treated with RF under conditions of 90°C for 7–10 min. Also, the RF heating therapy exhibited a high efficiency on aflatoxin B1 decontamination with a reduction of 69.6% in corn grains (Zhang & Wei, 2018). In this study, the disinfection of contaminated peanuts was done at selected electrode height and conveyor speed combination to check the efficacy of RF against aflatoxins, and the obtained results (Table 6) showed that RF treatment is effective against aflatoxin B1 and B2, with a pronounced decrease of aflatoxin B1 and B2 of 92.64% and 90.51%, respectively, at 89.96°C.…”
Section: Resultsmentioning
confidence: 99%